Between Theocracy and Pluralism: Identity Politics and Local Leadership in Indonesia - Sulistiyo, Heru (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2025)
The rise of religious-based identity politics in Indonesia has significantly influenced local governance, particularly among regional heads who integrate Islamic values into public administration. Conversely, the principle of pluralism—as a cornerstone of democracy—demands inclusivity and equal treatment for all societal groups. This study aims to examine and compare two leadership models of regional heads in Indonesia: one oriented toward Islamic theocracy and the other toward democratic pluralism, with a focus on their respective implications for the development of modern civil society. Employing a qualitative comparative case study approach, the research analyzes two regions with distinct leadership orientations. Data were collected through in-depth interviews, document analysis, and participant observation. The findings reveal that theocratic leadership emphasizes religious values and moral accountability, often enhancing religious identity but risking exclusion and limited civic space. In contrast, pluralist leadership promotes diversity and participatory governance, yet faces challenges in building a cohesive collective identity. The study concludes that effective local governance in a diverse society requires a balanced integration of moral-religious values and inclusive democratic principles to ensure fairness, legitimacy, and sustainability in civil society development.